Evaluation of Computer Skills Education Program PKBM Bina Insani Bandung - Pusya, Bunga Meila; Wahyudin, Uyu; Sukmana, Cucu (Indonesian Journal of Adult and Community Education, 2023)
The rapid development of information technology today makes a person left behind if they do not have quality resources capable of maximizing the utilization of this information technology. Therefore, many computer skills education programs are needed by today's society. The evaluation of the computer skills education program aims to determine the running of the program that has been implemented and also the results achieved by the program as well as to add insight and experience for me as a Community Education student in evaluating Community Education programs. Evaluation of this computer skills education program uses the CIPP evaluation model (Context, Input, Process, Product). This method is appropriate because in the success of training programs the reference is to adapt the program to the needs of the community and learning outcomes that can grow and create new skills. From the results of the evaluation carried out on the program, overall this program has been running well.